Comprehensive genome- and transcriptome-wide analyses of mutations associated with microsatellite instability in Korean gastric cancers - Yoon, Kwiyeom; Lee, Sunghoon; Han, Tae-Su; Moon, So Yeon; Yun, Sun Mi; Kong, Seong-Ho; Jho, Sungwoong; Choe, Jinny; Yu, Jieun; Lee, Hyuk-Joon; Park, Ji Hyun; Kim, Hak-Min; et al.

(untitled) (Genome Research, 2013)
Microsatellite instability (MSI) is a critical mechanism that drives genetic aberrations in cancer. To identify the entire MS mutation, we performed the first comprehensive genome- and transcriptome-wide analyses of mutations associated with MSI in Korean gastric cancer cell lines and primary tissues. We identified 18,377 MS mutations of five or more repeat nucleotides in coding sequences and untranslated regions of genes, and discovered 139 individual genes whose expression was down-regulated in association with UTR MS mutation. In addition, we found that 90.5% of MS mutations with deletions in gene regions occurred in UTRs. This analysis emphasizes the genetic diversity of MSI-H gastric tumors and provides clues to the mechanistic basis of instability in microsatellite unstable gastric cancers.